2019
DOI: 10.1155/2019/4610498
|View full text |Cite
|
Sign up to set email alerts
|

Imported Plasmodium vivax Malaria in the Russian Federation from Western Sub-Saharan Africa

Abstract: Background. Imported cases of Plasmodium vivax malaria from western Africa are reported annually in the Russian Federation. Infected native African people moving from western Africa for different purposes (students, businessmen, specialists, etc.) or Russian citizens (tourists, diplomats, businessmen, etc.) incubate the pathogen until reaching their Russian destination. Methods. All imported and other confirmed malaria cases and the associated Plasmodium species recorded over the past twenty years throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…They reported the contribution of these immigrants to the transmission of malaria to the United States (17). Also, in another study by Baranova et al in Russia, the role of immigrants to transmit malaria to inhabitants was confirmed (15). It should be noted that the same method as the current study was employed in these studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…They reported the contribution of these immigrants to the transmission of malaria to the United States (17). Also, in another study by Baranova et al in Russia, the role of immigrants to transmit malaria to inhabitants was confirmed (15). It should be noted that the same method as the current study was employed in these studies.…”
Section: Discussionsupporting
confidence: 64%
“…There are a number of published studies in other countries investigating immigrants as asymptomatic malaria cases. In these studies, researchers attempted to evaluate the role of immigrants in malaria transmission in Russia, Bulgaria, United States and Canada (15)(16)(17)(18). The key aim of this research was to monitor and detect immigrant's asymptomatic malaria cases in Bandar Abbas.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have elucidated the role of plants against anthelmintic in traditional medicine [ 100 , 101 , 102 ]. However, a wide range of molecules isolated and identified from plants have shown promising activity against multiple parasites [ 103 , 104 , 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 respondents who did take precautions against contracting malaria, five indicated that they would only do so again on their next trip to a malaria area if it was in the rainy season/summer. One respondent (respondent 11) stated that they would not take any precautions, as they believed that: risk is not significantly high when travelling for short time periods This is a misconception, and studies of imported cases of malaria in Europe and the Middle East resulting from tourists’ short trips to southern Africa underscore this (see Ben-Ami et al 2005 ; Baranova et al 2019 ). These erroneous sentiments are particularly concerning given the large proportion of respondents who obtain information on malaria risk from family, friends, and colleagues instead of government publications (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following discrete epidemics, this has been facilitated through tourism operators distributing information (Maartens et al 2007 ), but this would not address tourists staying in less formalized accommodation. The incorrect perceptions that malaria risk is not high when travelling for short periods (see Ben-Ami et al 2005 ; Baranova et al 2019 ), or can be mitigated through wearing long clothing only in the evenings, reveal the dangers of relying on non-official sources of information when planning precautionary measures to avoid malaria (Raman et al 2016 ). These respondents appear to have misunderstood that while the longer the visit to a malaria-prone region, the greater the risk, short stays do not carry no or low risk; likewise, while long clothing is advised at all times, wearing it for short periods is not sufficient in preventing the risk of bites or malaria (Baker 2018 ).…”
Section: Discussionmentioning
confidence: 99%